2017
DOI: 10.1128/mbio.02285-16
|View full text |Cite
|
Sign up to set email alerts
|

A Ferredoxin- and F 420 H 2 -Dependent, Electron-Bifurcating, Heterodisulfide Reductase with Homologs in the Domains Bacteria and Archaea

Abstract: Heterodisulfide reductases (Hdr) of the HdrABC class are ancient enzymes and a component of the anaerobic core belonging to the prokaryotic common ancestor. The ancient origin is consistent with the widespread occurrence of genes encoding putative HdrABC homologs in metabolically diverse prokaryotes predicting diverse physiological functions; however, only one HdrABC has been characterized and that was from a narrow metabolic group of obligate CO2-reducing methanogenic anaerobes (methanogens) from the domain A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 65 publications
2
54
0
Order By: Relevance
“…It has been suggested that HdrABC/FrhB catalyzes the confurcation of electrons from CoM-SH, CoB-SH, and Fd red to F 420 ( 7 ). Interestingly, in the present data set, four copies of hdrA were identified, two of which were fused with mvhD (see also reference 8 ). Furthermore, a gene cluster was identified that contains hdrABC as well as frhB and two copies of mvhD , with mvhD possibly being involved in electron transfer.…”
Section: Genome Announcementmentioning
confidence: 53%
“…It has been suggested that HdrABC/FrhB catalyzes the confurcation of electrons from CoM-SH, CoB-SH, and Fd red to F 420 ( 7 ). Interestingly, in the present data set, four copies of hdrA were identified, two of which were fused with mvhD (see also reference 8 ). Furthermore, a gene cluster was identified that contains hdrABC as well as frhB and two copies of mvhD , with mvhD possibly being involved in electron transfer.…”
Section: Genome Announcementmentioning
confidence: 53%
“…2). Two alternative sources can be envisioned: first, Fpo could produce F 420/red (standard reduction potential [E 0 =] ϭ Ϫ360 mV) using reduced methanophenazine (E 0 = ϭ Ϫ165 mV) as the electron donor via reverse electron transport driven by the proton motive force; second, a soluble heterodisulfide reductase could produce F 420/red via electron bifurcation using CoM-S-S-CoB and Fd red as the substrates (as suggested previously [22,23]). In the former mechanism, reduced methanophenazine would be derived from H 2 using Vht; in the latter, Fd red would be derived from H 2 via Ech.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding the flavin-harboring HdrA subunit is not only found in methanogenic and methanotrophic archaea (Costa et al, 2013 ; Costa and Leigh, 2014 ; Lang et al, 2015 ; Browne et al, 2017 ; Yan et al, 2017 ) but also in sulfate reducing anaerobic bacteria and archaea (Grein et al, 2013 ; Meyer et al, 2013 , 2014 ; Price et al, 2014 ; Ramos et al, 2015 ; Otwell et al, 2016 ), sulfur-oxidizing bacteria (Mangold et al, 2011 ; Grein et al, 2013 ; Liu et al, 2013 ), strict anaerobes having the capacity to degrade aromatic compounds (Boll et al, 2014 , 2016 ), Syntrophorhabdus aromaticivorans (Nobu et al, 2015 ) and some acetogenic bacteria (Mock et al, 2014 ).…”
Section: Finding Of 10 Other Electron-bifurcating Flavoenzyme Complexmentioning
confidence: 99%